Failure Mechanism and Optimization of Arch-Bolt Composite Support for Underground Mining Tunnel - Yuchun Mei; Weiteng Li; Ning Yang; Gang Wang; Tingchun Li; Linlin Sun (Advances in Civil Engineering)
Numerical simulation tests were performed on the arch-bolt combined supported mining tunnel through an improved numerical simulation approach. The typical soft rock roadway was took as the background, and the influencing factors such as ground stress level, lateral pressure coefficient, and support type and parameters were considered. The failure mechanism of a semicircular roadway with two straight walls was analyzed; results showed that the arch legs’ inward bending deformation and the arch-rock separation are the breakthrough of the global failure of the supporting system, and rock bolts breakage promoted the failure process. The effects of different controlling measures were analyzed including enlarging the bolt diameter, replacing the conventional bolts with energy-absorbing bolts, and setting arch locking bolts on the arch legs. The field test of the concrete-filled steel tube (CFST) arch-bolt composite support scheme was carried out in a high-stress soft rock roadway, and the results indicate the reliability of the main conclusions.